Juridical Analysis of the Crime of Murder Due to Overmacht in the Perspective of Criminal Law - Van Lodewijk Purba; Chivron Saragih; Jenriswandi Damanik (Program Pascasarjana UIN Sumatera Utara, 2023)
In social life, humans are always faced with various legal norms that are obeyed and obeyed, because the legal norms contain a rule that becomes a reference or life guide for each individual. One of the objectives of legal norms is to establish safety and order in society. These legal norms are sometimes born in the form of orders to be carried out and sometimes born in the form of prohibitions to be avoided or not done. One of the legal norms born in the form of prohibition is the crime of murder which is regulated in criminal law. Law enforcement in Indonesia, guidance and direction, need to be done so that the law is able to meet the needs in accordance with the level of progress of Indonesian society. Law enforcement is the responsibility of all levels of society and especially those who have an interest in the law because everyone is considered to know and at least feel what is called the law.